ANALYZING VIRTUAL ATMOSPHERIC OF TOKOPEDIA USING IMPORTANCE-PERFORMANCE ANALYSIS - Brenda, Wowor; Lapian, S.L.H.V.Joyce; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Internet is experiencing explosive growth over these past few year and become a fast-growing business that resulted in online shopping trend. Tokopedia as one of the popular e-commerce in Indonesia provides online selling experience to the sellers and their customer. This research aims to analyze the Virtual Atmospheric of Tokopedia. The type of this research is descriptive with quantitative approach and IPA used as the measurement tool. The sample size of this research is 100 respondents who are the customer of Tokopedia. The sampling method used in this research is purposive sampling by distributing online questionnaire to the customer. The result of the Virtual Atmospheric shows that Percentage of White Space and Font attributes are important to the customers and the company delivered a good performance to the customers, these attributes are located in Quadrant II. Meanwhile, Background Color and Color Scheme attributes are located in Quadrant III with low importance and low performance level. Based on the result of this study, it is wise for web store owner, in this case Tokopedia, to pay more attention for its virtual atmospheric aspect as it has an influence on customer behavior. A better virtual atmospheric performance could lead to customer attraction and increasing sales.Â ÂÂKeywords: importance and performance analysis, virtual atmospheric, tokopedia.